Justice and power relations in urban greening: can Lisbon’s urban greening strategies lead to more environmental justice? - Verheij, Jessica (2020)
As urban greening has become a prevalent tool in the context of global climate governance, this paper examines Lisbon’s greening strategies in the context of its election as European Green Capital 2020. While applying an analytical framework based on environmental justice, we perform a cross-analysis of the city-wide greening strategies, together with a peculiar and unusual planning process for a new green space in the neighbourhood of Marvila. Based on qualitative research carried out in-situ, we argue that Lisbon’s greening strategies are based on a discourse of ecological benefits, without aiming to ensure access to green space for different population groups. Procedural justice concerns are widely undervalued, resulting in limited space available for community involvement. We show how urban greening is essentially a multiscalar exercise, impacted by and affecting multiple scales simultaneously. Hence procedural justice deserves a much more prominent role in urban greening, as participation and recognition can give local communities the opportunity to adapt global urban agendas toward their particular needs and desires. Our findings lead us to conclude that environmental justice is ultimately an exercise of multiscalar governance, where local decision-making needs to attend to contextual challenges but also to a long-term sustainability vision at a larger scale.